Seismic retrofit of precast soft-storey building using diagonal steel-shape memory alloy bracing device: Numerical investigation. Issue 3 (February 2019) - Liu, Xiaoxian; Tsang, Hing-Ho; Wilson, John L
A diagonal steel-shape memory alloy bracing device is proposed for seismic retrofitting of vulnerable building frame structure. Superelastic shape memory alloy bar is put in series with steel bars in the bracing. The device makes use of the loading plateau of superelastic shape memory alloy to limit the tensile force of diagonal bracing. A precast soft-storey building frame in Australia was selected for a case study. A numerical model of the frame was developed and validated with the results from full-scale pull-down field tests. Nonlinear time history analysis was then conducted to evaluate the seismic performance of the frame with different retrofitting strategies. The result shows that the diagonal steel-shape memory alloy bracing can reduce the displacement demand on the soft-storey frame. Meanwhile, the level of tensile force of steel-shape memory alloy bracing can be controlled by the force plateau of the shape memory alloy bar, which is recommended to be 20% of the yielding force of the steel bar. The lower tensile force demand could alleviate the force demand at the associated support connections.